(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Artificial intelligence (AI) and health informatics are transforming nursing practice globally. However, adoption often progresses unevenly, with frontline staff perspectives underrepresented. This qualitative study explored Saudi nurses’ views on using AI/informatics to augment clinical roles. Semi-structured interviews were conducted with 30 nurses from diverse hospital roles and departments in Riyadh. Transcripts were analyzed using thematic analysis. Participants recognized potential benefits of AI/informatics including enhanced efficiency, improved care coordination, reduced errors, and clinical decision support. However, they held concerns about over-reliance on technology, compromised nursing judgment, dehumanization of practice, and skills erosion. Realizing benefits required addressing barriers like inadequate user education, poor system design, and gaps informing developers on nursing needs. Recommendations encompassed greater staff involvement in system selection/development, robust end-user training on capabilities/limitations, and targeted education on informatics competencies within nursing curricula. Despite advantages, integrating AI/informatics into practice also risks alienating nurses from their expertise. Strategic efforts addressing identified challenges and misunderstandings can help smooth adoption among Saudi nursing professionals.